A study of maternal factors influencing birth weight in newborn in a tertiary care hospital - S., Anu M.; Senguttuvan, Aravinth; K., Dheepane; Raghupathy, N. S. (International Journal of Contemporary Pediatrics, 2021)
Background: Low birth weight (LBW) is a major public health problem which needs to be addressed. The maternal factors play a major role in the child’s weight. The main aim is to identify the risk factors in the mother and appropriately manage so as to reduce the effects on children. Aim was to study the maternal risk factors influencing the weight of the baby in a tertiary care hospital at Pondicherry. Methods: A total of 225 babies were included in the study. Birth weight was recorded within 30 minutes after birth. Mother’s details were collected using a questionnaire. The collected data was analyzed using statistical package for the social sciences (SPSS) version 21. Results: A total of 225 babies and their mothers were enrolled in the study where 124 were males and 101 were females. 204 were term and 21 were preterm. Mean age of the mothers was 22.52±3.33 years, mean weight noted was 62.94±10.09 kg and mean height was 160.1±7.15 cm. The study showed associations between birth weight and mother’s age, weight, height, hemoglobin (Hb) %, birth interval, income, bad obstetric history and complications. Conclusions: This study concluded that maternal factors are associated with birth weight owing to mother’s age, weight, height, anemia, birth interval, bad obstetric history with complications and family income. This calls for better management of mothers at the initial stages of pregnancy to reduce LBW and morbidity and mortality. Health education and large-scale awareness programs implementation can reduce and prevent this public health problem.